The Effect of Sow Body Weight Change During Gestation on Sow Body Weight Change and Litter Average Daily Gain During Lactation - Ron Aldwin S. Navales; Weasley Orlando; Jiyao Guo; Lori Kociemba; Carine Vier; Joel M. DeRouchey; Katelyn N. Gaffield; Jordan T. Gebhardt; Mike D. Tokach; Jason C. Woodworth (Kansas Agricultural Experiment Station Research Reports, 2025)
A retrospective study was conducted to assess the impact of sow BW change during gestation on sow BW change and litter ADG during lactation. Data from 1,978 gilts and sows across three studies were categorized by parity (gilts: n = 1,098; sows: n = 880). Maternal BW gain during gestation was calculated as the difference between estimated BW at 24-h post-farrowing and BW at d 1 of gestation, while lactation BW change was determined as the difference between BW at weaning and estimated BW at 24-h post-farrowing. Litter ADG was calculated as the difference between litter weight at weaning and litter weight after cross-fostering, divided by lactation length. Regression analyses were performed to model gestation BW change as a function of sow BW at d 1 of gestation, lactation BW change as a function of gestation BW change, and litter ADG as a function of gestation and lactation BW change, along with other covariates. Final models were selected using the Akaike Information Criterion (AIC). Results indicated that in both parity categories, sow BW at day 1 of gestation was negatively associated with gestation BW change (P < 0.05), and gestation BW change was negatively associated with lactation BW change (P < 0.05). Conversely, litter ADG was positively related to both gestation and lactation BW gain (P < 0.05). In gilts, the effect of gestation BW change on litter ADG was modest and can be explained by the offsetting effect of lactation BW change that is negatively influenced by gestation BW change. In contrast, the offsetting effect of lactation BW change on the relationship between gestation BW change and litter ADG was less substantial in sows. In conclusion, the dynamics of sow BW change during gestation and lactation significantly influence litter ADG. Increased BW gain in gilts during gestation led to greater BW loss in lactation without negatively affecting litter ADG, whereas BW loss in sows during gestation led to compensatory gain during lactation at the expense of litter ADG.
Keywords: gestation; lactation; litter average daily gain; sow body weight